2018
DOI: 10.3889/oamjms.2018.380
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Concordance of Medication-Taking Behaviour in Tuberculosis Patients in Medan, Indonesia

Abstract: AIM:This study aimed to analyse tuberculosis (TB) medication-taking behaviour based on the concept of concordance between health workers and TB patients in Medan, Indonesia.METHODS:This study was an analytical study with a cross-sectional design. A total of 100 patients undergoing TB treatment at several public health centres in Medan City participated in the study.RESULTS:The results showed that there was a relationship between the concordance behaviour of the health workers with the attitude and medication-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 6 publications
1
6
0
Order By: Relevance
“…Another study has also concluded that the level of knowledge about the disease affects the patient's adherence to medication [5]. However, this is different from the study of Wahyuni et al, (2018) [6], which states that there was no association between knowledge and medication adherence, this might be because patients had received a lot of information from various sources not only from medical workers. It has also been proven that increasing patient knowledge, both about their disease and about the drugs consumed, will result in better compliance with the drug.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Another study has also concluded that the level of knowledge about the disease affects the patient's adherence to medication [5]. However, this is different from the study of Wahyuni et al, (2018) [6], which states that there was no association between knowledge and medication adherence, this might be because patients had received a lot of information from various sources not only from medical workers. It has also been proven that increasing patient knowledge, both about their disease and about the drugs consumed, will result in better compliance with the drug.…”
Section: Discussionmentioning
confidence: 92%
“…Similarly, a study by Wahyuni et al, (2018) [6] which states that the main factor linking patients to behavioral compliance is the patient's attitude to treatment (p ≤ 0.05). Of the 55% of patients who adhere to treatment, 67% have a positive attitude (good).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another term that has been commonly used in studies related to treatment adherence is concordance. Concordance refers to harmonious cooperation or agreement between patients, doctors, and healthcare workers regarding treatment plans and action, mainly focused on consultation and negotiation [ 17 ]. It is an approach taken by parties related to patient management to ensure the patients are well informed about the diagnosis and treatment, understand their benefits and risks, and assist in their decision to optimize the potential use of medical care.…”
Section: Definition Of Anti-tb Medication Adherencementioning
confidence: 99%
“…The non-modifiable factor has been closely related to non-adherence to medication, including male gender [ 20 ], younger age [ 20 , 29 , 30 ], and marriage status (being divorced and widowed) [ 28 ]. On the other hand, modifiable factors include psychological and cognitive factors (forgetfulness, lack of knowledge, perceived barrier, psychological distress, and stigma) [ 17 , 28 , 29 , 31 , 32 ], and behavioral factors (alcohol and cigarette smoking use [ 23 ] are associated with non-adherent to TB medications. In addition, social acceptance of traditional medicine and a lack of family support have been recognized as key factors in non-adherence to anti-TB treatment regimens [ 33 ].…”
Section: Factors Contributing To Anti-tb Medication Adherencementioning
confidence: 99%